Soil suitability evaluation for mango, citrus and guava in Hosangabad district, Madhya Pradesh using geo spatial technology - GAHLOD, N. S.; ARYA, V. S.; KUMAR, Y. SURESH; ., RAVI (Journal of Soil and Water Conservation, 2021)
The information on soil and land characteristics is pre-requisite to develop an optimal land use plan on sustainable basis. The suitability analysis for a particular crop helps planners to develop a crop management system and to identify the limiting factors of crop production in that area. Soil suitability evaluation for different land utilization types was carried out to assess the suitability of Mango, Citrus and Guava crops in Hosangabad District of Madhya Pradesh. The database on soil and land use/land cover was generated using IRS-1D, LISS-III satellite data. Soil samples were analyzed for their physicochemical properties. The generated data and the soil properties were integrated and analyzed with the suitability criteria of Mango, Citrus and Guava in geographical information system (GIS) environment. A qualitative approach has been used to classify the land on the basis of criteria laid down for various suitability classes viz. S1- Highly suitable, S2-Moderately suitable, S3- Marginally suitable, N-Not Suitable. It was found that out of the total geographic area of the study i.e. 669844.61 ha, only 6.26 per cent area is moderately suitable and 45.41 per cent area is marginally suitable for citrus, 28.23 per cent moderately and 22.52 per cent marginally suitable for Mango and 14.31 per cent area is marginally suitable for guava cultivation.